Apelin concentrations are associated with altered atherosclerotic plaque stability mediator levels and atherosclerosis in rheumatoid arthritis. (January 2017) - Gunter, Sule; Solomon, Ahmed; Tsang, Linda; Woodiwiss, Angela J.; Robinson, Chanel; Millen, Aletta M.E.; Norton, Gavin R.; Dessein, Patrick H.
Abstract: Background and aims: Apelin-APJ signaling reduces cardiovascular disease (CVD) risk. In rheumatoid arthritis (RA), the atherosclerosis burden and plaque vulnerability to rupture are increased. We explored relationships between apelin concentrations and subclinical CVD in RA. Methods: Apelin levels were measured in 235 (114 black, 121 white) RA patients. Associations between apelin concentrations and ultrasound determined carotid artery intima-media thickness (cIMT) and plaque, and levels of matrix metalloproteinase (MMP)-2 and -9 that mediate plaque stability and vulnerability respectively, were identified in confounder adjusted multivariate regression analysis. Results: In all patients, apelin concentrations were directly associated with those of MMP-2 (β (SE) = 0.324 (0.112), p  = 0.004) and inversely with those of MMP-9 (β (SE) = -0.239 (0.060), p  = 0.000). Apelin concentration-subclinical CVD relations were influenced by population origin, RA disease activity, erythrocyte sedimentation rate (ESR) and interleukin (IL)-6 concentrations (interaction p  = 0.001 to 0.04). Accordingly, the apelin-MMP-2 concentration relationship was reproduced in white (β (SE) = 0.367 (0.146), p  = 0.01) but not black RA patients (β (SE) = 0.197 (0.220), p  = 0.4), and only in those without (but not with) large erythrocyte sedimentation rates (β (SE) = 0.428 (0.143), p  = 0.003) or interleukin-6 levels (β (SE) = 0.485 (0.288), p  = 0.04). By contrast, the apelin-MMP-9 concentration relation was reproduced more consistently. Apelin levels were inversely related to cIMT in patients with RA remission or mild (β (SE) = -0.068 (0.033), p  = 0.04) but not moderate or high disease activity (β (SE) = 0.015 (0.112), p  = 0.7). Conclusions: Apelin concentrations are associated with altered plaque stability mediator levels and atherosclerosis in patients with RA. These relations are partially dependent on population origin and systemic inflammatory status. Highlights: Apelin is associated with favorable plaque stability mediator level profiles in rheumatoid arthritis (RA). Apelin is related to decreased atherosclerosis in patients with RA. Population origin and inflammation influence apelin-subclinical cardio-vascular disease (CVD) relationships.